Current barriers and ethical considerations for clinical implementation of epidural stimulation for functional improvement after spinal cord injury. (2nd September 2020) - Solinsky, Ryan; Specker-Sullivan, Laura; Wexler, Anna
Abstract : Context/objective : To determine current barriers for clinical implementation of epidural stimulation for functional improvement after spinal cord injury and highlight applicable ethical constructs to approach future research. Design : Survey of spinal cord injury medicine physicians, January 2019. Setting : Spinal cord injury model systems hospital sites across the United States. Participants : Spinal cord injury medicine physicians. Interventions : NA. Outcome measures : Physician-identified current barriers to clinical implementation of epidural stimulation. Results : The response rate for the survey was 54.6% ( n  = 42), with the majority of physicians (61.9%) having been asked by patients with spinal cord injuries about epidural stimulation. Numerous current barriers to clinical implementation were identified, including need for additional efficacy studies (92.9%), lack of clear guidelines on stimulation parameters (83.3%), and inability to identify which patients will benefit (76.2%). Conclusions : With multiple barriers to clinical implementation currently identified, evaluating this research with an eye toward the ethical construct of equipoise is increasingly relevant. Addressing these barriers may require modifications in both physician expectations and how researchers approach this work.